Mood disorders in Huntington's disease: from behavior to cellular and molecular mechanisms - Pla, Patrick; Orvoen, Sophie; Saudou, Frédéric; David, Denis J.; Humbert, Sandrine (Frontiers in Behavioral Neuroscience, 2014)
Huntington’s disease (HD) is a neurodegenerative disorder that is best known for its effect on motor control. Mood disturbances such as depression, anxiety, and irritability also have a high prevalence in patients with HD, and often start before the onset of motor symptoms. Various rodent models of HD recapitulate the anxiety/depressive behavior seen in patients. HD is caused by an expanded polyglutamine stretch in the N-terminal part of a 350 kDa protein called huntingtin (HTT). HTT is ubiquitously expressed and is implicated in several cellular functions including control of transcription, vesicular trafficking, ciliogenesis, and mitosis. This review summarizes progress in efforts to understand the cellular and molecular mechanisms underlying behavioral disorders in patients with HD. Dysfunctional HTT affects cellular pathways that are involved in mood disorders or in the response to antidepressants, including BDNF/TrkB and serotonergic signaling. Moreover, HTT affects adult hippocampal neurogenesis, a physiological phenomenon that is implicated in some of the behavioral effects of antidepressants and is linked to the control of anxiety. These findings are consistent with the emerging role of wild-type HTT as a crucial component of neuronal development and physiology. Thus, the pathogenic polyQ expansion in HTT could lead to mood disorders not only by the gain of a new toxic function but also by the perturbation of its normal function.